RARE-19. Molecular characterization and treatment response of metastatic DIA/DIG. (3rd June 2022) - Petropoulos, James; Finkbeiner, Melanie; Assis, Zarina; Gallagher, Clare; Hader, Walter; Chan, Jennifer; Strother, Douglas; Lafay-Cousin, Lucie
Abstract: INTRODUCTION: Desmoplastic infantile astrocytoma (DIA) and desmoplastic infantile ganglioglioma (DIG) are glioneuronal tumors of early childhood. Surgical resection is usually sufficient to cure these benign tumors. The presence of metastatic seeding is rare and has been reported as an adverse prognostic factor. We present 2 cases of young children with recurrent metastatic DIA/DIG to describe their presentation, therapeutic management and outcome and to highlight the importance of molecular characterization of these rare tumors to guide adjuvant therapy. CASES DESCRIPTION: The first patient developed metastatic recurrence after initial gross total resection (GTR) of a localized DIG. The disseminated relapse was treated with monthly carboplatin and vincristine (CB/VCR). Complete response was achieved after 15 cycles and the patient has remained in continuous complete remission for 5 years. Post hoc molecular analysis of the tumor revealed a BRAF-RDX fusion. The second patient presented with a disseminated intraventricular relapse following an incomplete resection of a DIA associated with a SPECC1L-NTRK2 fusion. The patient received 2 cycles of CB/VCR with minimal response and was then switched to Larotrectinib leading to a very good partial response (VGPR) 3 months into therapy and has remained on treatment since then with significant clinical improvement. DISCUSSION/ CONCLUSION: In our 2 cases, metastatic recurrence was responsive to adjuvant therapy leading to complete response with conventional chemotherapy in the first one and to VGPR with NTRK inhibitor in the second patient. Early molecular characterization of these benign tumors is critical in case of incomplete resection or metastatic seeding to widen therapeutic options and maximize chance of cure. Response with NTRK inhibitor appears rapid and significant but the total duration of treatment and sustainability of response after discontinuation remain unknown.